ONTOGENY OF THE BALASHARK Balantiocheilos melanopterus BLEEKER, 1851 (CYPRINIDAE) - Etienne Baras; Agus Priyadi; Marc Legendre (Indonesian Aquaculture Journal, 2007)
The Balashark is a highly praised ornamental species that has been overfished to the point that it has become endangered in most of its distribution area, especially in Indonesian waters. Captive propagation has reduced the threats upon wild populations of balashark. Nevertheless, knowledge on the biology of this species is still scarce, in particular as regards to its ontogeny. This information is crucial for the identification of larvae and small juveniles in the wild, as well as for improving its culture. Balashark eggs average 1.2-1.3 mm in diameter and hatch after 13 hours (26-28°C), giving birth to 4.5-mm embryos, with a yolk sac of circa 1.1 mm3. At the end of the endogenous feeding period (day 4 after hatching [AH]), larvae attain 6.3 mm TL. The mouth opens on day 2 AH (5.8 mm total length, TL). At the time of first feeding (day 4 or 5 AH, 6.3 mm TL), their mouth and gape already average 0.5 mm and 0.27 mm, respectively, and they grow up to 10.2 and 6.3% TL, respectively, on day 8 AH. The swim bladder starts forming as early as day 2 AH and is filled by day 3 AH (5.9 mm TL), but the separation between the anterior and posterior chambers does not take place before 9.5 mm TL (day 9 or 10 AH). The fin development sequence is typical of cyprinids, and follows a caudal-to-cranial pattern (i.e.; caudal, dorsal and anal, pelvic then pectorals), except for the anlagen of pectoral fins, which are present in 1-day old fish (5.3 mm TL). Based on the vanishing of the abdominal and caudal fin fold, and on the lengths of the fins relative to fish size, the transition between the larval and juvenile stage occurs at circa 17 mm TL (corresponding standard length: 13.7 mm). At this stage, the scale cover is not developed yet, but juveniles already exhibit the typical pigmentation pattern of adults on their dorsal, anal, pelvic and caudal fins, while pigmentation on the pelvic fins is still in its very early stages.